Screening with Limited Information: A Dual Perspective - Chen, Zhi; Hu, Zhenyu; Wang, Ruiqin (Operations Research, 2024)
A Dual Perspective to the Robust Screening Problem Robust screening problem is concerned with the problem of a seller seeking a selling mechanism that maximizes the worst-case revenue obtained from a buyer whose valuation distribution lies in a certain ambiguity set. In the paper “Screening with Limited Information: A Dual Perspective”, Z. Chen, Z. Hu, and R. Wang show that strong duality holds between the problem of finding the optimal robust mechanism and a minimax pricing problem, where the adversary first chooses a worst-case distribution and then the seller decides the best posted price mechanism. The duality result connects prior literature that separately studies the primal (robust screening) and problems related to the dual and offers a unified geometric intuition in solving the problem.